PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV-A SD NEGERI 50 BABUSSALAM KECAMATAN MANDAU KABUPATEN BENGKALIS - Yesi, Erni; Marhadi, Hendri; Lazim N, Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is motivated by the poor results of students studying mathematics, can be seen from the results of learning math class IV-A SD Negeri 50 Babussalam, with the average value of the class 62.25. Therefore, the researchers provide an alternative implementation of cooperative learning model Teams Student Achievement Division (STAD) studying in class IV-A SD Negeri 50 Babussalam. This study aims to improve learning outcomes Math class IV-A SD Negeri 50 Babussalam the Implementation Model Cooperative Learning Teams type Student Achievement Division (STAD). Design research conducted PTK with 2 cycles. Data instrument consists of tools and instruments to learn to collect data. Based on the analysis of research data after applying cooperative learning model Student Team Achievement Division (STAD), the average percentage of teachers in the first cycle of activity increased 68.75% to 85.42% in the second cycle. The average percentage of student activity also increased, which is 54.12% in the first cycle increased to 79.17% in the second cycle. student learning outcomes in basic score with the average value of 62.25 and the first cycle increased with an average value of 80.5 class with an increasing percentage of learning outcomes 22.67% and the percentage of students who complete 75%, and the second cycle increased again with an average value of 90 with a percentage increase learning outcomes 30.83% and the percentage of students who complete 85%. These results show that the implementation of cooperative learning model Student Team Achievement Division (STAD) .Can improve learning outcomes Math class IV-A SD Negeri 50 Babussalam.Key Words: Student Teams Achievement Division, learning outcomes IPS